2019
DOI: 10.1088/1361-648x/ab4845
|View full text |Cite
|
Sign up to set email alerts
|

Structural, optical and magnetic properties of Sm3+ doped yttrium orthoferrite (YFeO3) obtained by sol–gel synthesis route

Abstract: Fine powders of Y 1−x Sm x FeO 3 (x = 0, 0.05, 0.10, 0.15) were synthesized via citrate based sol-gel route. While the as synthesized powders were amorphous, the calcined (900 °C/8 h) powders were confirmed to be polycrystalline by x-ray powder diffraction (XRD) studies. The calcined powders were found to crystallize in an orthorhombic structure associated with the lattice parameters a = 5.59 Å, b = 7.60 Å, c = 5.28 Å. These lattice parameters increased with the increase in Sm 3+ content at yttrium sites. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 38 publications
2
21
0
Order By: Relevance
“…Due to Yb doping concentration variations inhibits the growth of the grain boundaries and hinders the propagation of nucleation. 36 The agglomeration of particles increases with increase in Yb doping upto x = 0.10 concentration and the crystal size of the particle decreases with doping due to the strain induced. This resulted in densification of the particles.…”
Section: Morphological Analysismentioning
confidence: 98%
“…Due to Yb doping concentration variations inhibits the growth of the grain boundaries and hinders the propagation of nucleation. 36 The agglomeration of particles increases with increase in Yb doping upto x = 0.10 concentration and the crystal size of the particle decreases with doping due to the strain induced. This resulted in densification of the particles.…”
Section: Morphological Analysismentioning
confidence: 98%
“…32 The room temperature magnetization versus applied magnetic eld (M-H) loop of YFeO 3 suggests that it is an antiferromagnetic material. 12 The GKA (Goodenough, Kanamori and Anderson) rules predict the antiferromagnetic behaviour of YFeO 3 through oxygen mediated super-exchange interaction of pristine YFeO 3 . 33 As mentioned earlier, the d 5 There is an increase in magnetization with an increase in dopant concentration at Y 3+ .…”
Section: Magnetic Propertiesmentioning
confidence: 99%
“…However, it was demonstrated that the magnetic properties of YFeO 3 can be enhanced by means of doping. For instance, the non-magnetic Y 3+ is doped by divalent 10 and trivalent ions 11,12 and Fe 3+ by trivalent 13 and high valency ions. 14 Doping at Y 3+ resulted in the improvement of magnetization while the Fe 3+ doping enhanced the coercivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, P S J Bharadwaj et al prove that magnetization of YFeO 3 originated entirely from the canting of Fe 3+ moments, as Y 3+ being diamagnetic, cannot contribute to the magnetization. Regardless of replacement of Y ion by Sm ion, crystallite sizes are still greater than 100 nm [7]. On another side, where Liying Qi et al prepared Ca 0.75 Er 0.25 MnO 3 using different technique and doping A-site with different ions, but the effect of such dopants on magnetization and dielectric behavior didn't studied [8].…”
Section: Introductionmentioning
confidence: 99%